Trends in first‐trimester nausea and vomiting of pregnancy and use of select treatments: Findings from the National Birth Defects Prevention Study. Issue 1 (4th July 2020) - Schrager, Nina L.; Adrien, Nedghie; Werler, Martha M.; Parker, Samantha E.; Van Bennekom, Carla; Mitchell, Allen A.; ,
Abstract: Background: Although nausea and vomiting of pregnancy (NVP) is common, the secular and demographic trends of NVP and its treatments are not well‐studied. Objectives: To describe the prevalence and patterns of first‐trimester NVP and selected treatments among controls in the National Birth Defects Prevention Study (NBDPS). Methods: National Birth Defects Prevention Study is a population‐based case–control study of birth defects in the United States (1997‐2011). We collected self‐reported data about NVP and use of commonly reported pharmacological and herbal/natural treatments (ondansetron, promethazine, pyridoxine, metoclopramide, doxylamine succinate, ginger, phosphorated carbohydrate solution, and prochlorperazine) from mothers of non‐malformed control infants. We estimated the prevalence of NVP and selected treatments and examined secular and demographic trends (education, race/ethnicity, and maternal age) for such use, adjusting for study centre. Results: Among 10 540 mothers of controls, 7393 women (70.1%) reported first‐trimester NVP, and 12.2% of those used one or more of the commonly reported treatments. Specific treatment use varied after adjustment for study centre (ondansetron: 3.4%; promethazine: 4.2%; pyridoxine: 3.2%; metoclopramide: 0.7%; doxylamine succinate: 1.7%; ginger: 1.0%; phosphorated carbohydrate solution: 0.4%; and prochlorperazine: 0.3%). Treatment use increased for each agent over the study period. Women with more years of education reported more NVP and treatment use. White (72%), Hispanic (71%), and other race (73%) women reported more NVP than Black women (67%); White women used selected NVP treatments most frequently, and Black women used them more than Hispanic women. Though women aged 25‐34 years reported more NVP (72%) than younger (69%) or older (67%) women, the frequency of medication use was similar among women aged 25‐34 and ≥35, and lower among women aged <25 years. Conclusions: National Birth Defects Prevention Study controls reported NVP at frequencies similar to those previously reported. Of note, we observed an increase in use of selected treatments over time, and variations in NVP and treatments by study site and demographic factors.